Centro de investigación de ciencias biológicas en el municipio de Yumbo, Valle del Cauca (2020)
In this investigative work, an environmental problem caused by mining is taken into account, which has had a process that has been exploited for decades in this area located in Yumbo and also the industry that is located at its entrance, a place locate d in the south from Valle del Cauca; a place where this type of transmission by mining has been one of the main sources of factors for families from Yumbo. This environmental problem has irreversible damage to environmental damage in this area and so f ar there are major diseases in its inhabitants who operate in this sector and also due to the environment that the factories process, according to the aforementioned objectives that will respond or at least allowed to better manage what happens there; Peop le with less economic resources push them to continue exploiting this element for too low a standard payment and the constant exposure of these gases in such a way, which has damaged an increasingly greater damage in almost all movements.